Peran Public Ownership dalam Memoderasi Hubungan Growth Option, Investment Opportunity Set, Corporate Governance dengan Kinerja Keberlanjutan: Studi Empiris pada Sektor Barang Konsumen Primer di Bursa Efek Indonesia Tahun 2019-2023 - Wulandari, Fitri; Khotimah, Husnul; Luthfiah, Yussi Dwi; Febriyanto, Muhammad Ikhsan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research examines the influence of growth options on sustainability performance, the influence of investment opportunity sets on sustainability performance, the influence of corporate governance on sustainability performance in primary consumer goods sector companies on the Indonesia Stock Exchange. This research also examines the role of public ownership as a moderator. The research method used in this research is the Quantitative Research Method with Purposive sampling. By using the eviews program, this research has proven that the Investment Opportunity Set has an effect on sustainability performance, while Growth Options and Corporate Governance have no effect on sustainability performance. At the same time, this research also finds that public ownership can weaken the influence of corporate governance on sustainability performance.